(untitled) (Journal of International Studies, 2013)
Төв Азийн мал, мал аж ахуй, мал маллах арга технологи, ашиг шим болон орчин үеийн байдлыг тусган харуулсан. English title: Modern Animal Husbandry in Central Asia and Traditional Nomadic Knowledge of Animals